9th Mercosul Biennial | Porto Alegre: curatorial and spatial practices, a dialogue with Sofía Hernández Chong Cuy - Hernández Chong Cuy, Sofía; Sommer, Michelle (PORTO ARTE: Revista de Artes Visuais, 2017)
What sets the curatorial practice in a biennial exhibition model today? A question, among many others, raised during the project structuring of the 9th Mercosul Biennial | Porto Alegre, from September 13th to November 10th 2013, under the title, in Portuguese, "Se o Clima for Favorável" (in Spanish, "Si el tiempo lo permite"; in English, "Weather Permitting"), is contained in this interview with art director and general curator of this issue, Sofía Hernández Chong Cuy. The meeting, which took place during the unfolding of the event, shares with the reader the questions generated during the process of construction of a large-scale exhibition event. On one side, curating, and on the other, museography, considered from the professional activities performed by the ones involved in this conversation during the biennial edition, meet to, through open dialogue, establish an attempt to think critically about the experience of exhibition practices nowadays – amid design and materialization, debate and provocation, curatorial and artistic intentionality, interpretation and public presentation of contemporary art.